Impact of Music on Reducing Stress: A Case Study on Reducing Stress on Female Students of Universities - Palak Bagaria; Priyal Gupta; Shubhanshi Sharma; Sanjeev Patwa (International Journal of Mobile Computing Technology, 2024)
This case study explores the effects of music as a stress reduction tool for college students. Stress is a prevalent issue affecting the physical and mental well-being of students, with potential long-term consequences for their academic performance and overall health. This study employs a mixed-methods approach, combining surveys, and interviews to gather comprehensive data. A total of 100 students participated in our survey. The research focuses on assessing the relationship between music and stress reduction by examining the frequency and types of music listened to by students during stressful situations. Additionally, it explores the perceived impact of music on students’ stress levels and their coping mechanisms. The study also considers individual differences, such as music preferences and stress triggers, to better understand the nuanced effects of music on stress reduction. Further analysis and longitudinal studies are warranted to substantiate these initial findings and provide a comprehensive understanding of the role of music in reducing stress among university students.
Keywords: Anxiety; Music therapy; Stress reduction; emotional regulation; stress management tool